The Impacts Of Fatwa Awareness, Maqaṣid Al-Shari'ah Application, Religiosity And Utaut2 On The Adoption Of Online Media As A Fatwa Information Platform Among Malaysian Muslims - Mohd Harifadilah Rosidi (Universiti Sains Islam Malaysia, 2024)
Matric: 4201013(FSU)